Coronavirus pandemic and tourism: Dynamic stochastic general equilibrium modeling of infectious disease outbreak - Yang, Yang; Zhang, Hongru; Chen, Xiang (Annals of tourism research, 2020)
•We propose a DSGE model to examine the impact of the coronavirus outbreak on tourism.•The model is generalizable to any epidemic.•The model supports the policy of providing tourism consumption vouchers for residents.